Tafsir Maqashid Ayat-Ayat Al-Qur’an Dalam Fatwa DSN-MUI No. 150/DSN-MUI/VI/2022 Tentang Produk Asuransi Kesehatan Berdasarkan Prinsip Syariah - Prastyo, Edy; Nursobah, Achmad; Muhajir, Muhajir (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The Fatwa of the National Sharia Council - Indonesian Ulema Council (DSN-MUI) plays a crucial role in the development of sharia insurance products in Indonesia by providing relevant Islamic legal guidelines in response to contemporary practices. This article analyzes DSN-MUI Fatwa No. 150/DSN-MUI/VI/2022 concerning Sharia-Based Health Insurance Products through the perspective of Wahbah Az-Zuhaili's maqashid tafsir. This research employs a qualitative method based on a literature study to explore the values of sharia maqashid in Quranic verses, such as QS. Al-Maidah: 1, QS. Al-Baqarah: 279-280, and QS. Az-Zumar: 18 and 55. Regarding the implementation of the fatwa, five out of six indicators by Van Meter and Van Horn show that it has been in accordance with the provisions of the fatwa. However, from the aspect of the implementers' disposition, the researcher found practices that do not align with the fatwa's provisions. First, a portion of the premium funds from sharia health insurance products is used for investment. However, sharia health insurance products are non-saving products (not savings), and the entire tabarruk fund should be used as tabarruk. Second, the kafalah contract applied in sharia health insurance products does not align with the principle of taawun (mutual assistance) among participants. This is because the purpose of someone joining sharia insurance is to help other participants in the event of a risk. The implementation of the kafalah contract eliminates the principle of mutual assistance among participants, as the participant making a claim must bear the cost themselves. Moreover, before becoming a participant, they have already undergone the underwriting process. Third, there is a requirement to register as a participant for those who wish to conduct research in Takaful. These three points contradict the principle of taawun in sharia insurance and the principle of tara’d|in (consent) in sharia economic law.